Hot Formability of Heat-Resistant Stainless Steel X15CrNiSi 20-12 - Kawulok, R.; Schindler, I.; Navrátil, H.; Ševčák, V.; Sojka, J.; Konečná, K.; Chmiel, B. (Archives of Metallurgy and Materials, 2020)
High-temperature plastic properties of heat-resistant stainless steel X15CrNiSi 20-12 were assessed on the basis of hot tensile tests and nil strength tests. The results were supported by metallographic analyses using SEM and EDX analysis. The formability of the investigated steel can be divided into roughly three temperature areas. In the temperature range of 900°C to about 1050°C, formability was negatively affected by precipitation of carbide particles at grain boundaries. As the temperature rose to 1200°C, these particles dissolved, resulting in an increase in formability. Further temperature increases resulted in a relatively steep drop in formability caused by overheating of the material. The nil ductility temperature of 1280°C and the nil-strength temperature of 1362°C were determined. The Plastic and strength properties of the investigated material were compared with the deformation behavior of the reference steel X5CrNi 18-10, which shows a significantly wider range of suitable forming temperatures.
Keywords: Heat-resistant stainless steel; Hot tension test; Nil strength temperature; Nil ductility temperature